Effect of Copper Azole Preservative on the Surface Wettability and Interlaminar Shear Performance of Glulam Treated with Preservative - Shuyan Wang; Hang Zhang; Jingqiu Xie; Qianning Wang; Ao Zhang; Xiaojun Yang (BioResources, 2024)
The application of copper azole (CA) preservative on glulam can improve the durability of the material. The effect of CA preservative was evaluated relative to the surface bonding quality of laminates with different surface conditions. The surface morphology and wettability of CA preservative-treated laminates were analyzed. A comparison was made on the interlaminar shear strength of preservative-treated glulam under varying environmental conditions. The atomic force microscope (AFM) diagrams showed that CA preservative adhered to the wood fibers’ surface and filled some wood cell cavities, thus reducing the water permeability of the treated laminate. Planing effectively enhanced the surface wettability of the preservative-treated laminate. The tiny particles of CA preservative on the planed laminate surface were distributed relatively uniformly, with a proportion smaller than that of the unplaned laminate. Furthermore, the interlaminar shear strength of preservative-treated glulam using planed laminates was at least 15% higher than that of unplaned laminates. In both hot and humid environments and natural aging tests, preservative-treated glulam bonded with resorcinol formaldehyde (RF) adhesive outperformed those bonded with polyurethane (PUR) adhesive. To ensure reliable quality of preservative-treated glulam, it is recommended to plane the laminate by 0.6 mm and use RF adhesive.